STUDENTS' OBSTACLES IN PRACTICING SPEAKING ENGLISH : A Case Study at Batam Polytechnic - Togatorop, Erikson (2009)
The fact that many students get reluctant to practice speaking English has become a dilemma in ESL/EFL teaching, since teachers and students realize that speaking is a language skill that does need practice. There must be serious reasons why they are reluctant to do this practice. The purpose of this study was to find out the obstacles that hinder the students from practicing speaking English, conducted at Batam Polytechnic, particularly the students of the second semester. More specifically, this study explored the following questions: (1) What are the students' obstacles in practicing speaking English from the students' point of view? (2) What are the students' obstacles in practicing speaking English from the lecturers' point of view? and (3) What are the possible solutions to those obstacles? This study employed a qualitative descriptive research in which the data were collected by questionnaires and interviews. The researcher distributed the questionnaire to the students to find out why they got reluctant to practice speaking English, and finally did interviews with the English lecturers to validate the data gained from questionnaires. The study found three categories of students' obstacles in practicing speaking English: a) the obstacles related to the students themselves - lacking of English ability and the inability to manage emotion; b) the obstacles related to the lecturers - the lecturers' giving limited time for students to practice and their fully English teaching; and c) obstacles related to the environment - the limited English input and the lack of partner to practice speaking English. Based on the research findings, it was then recommended for the lecturer 1) to encourage and to give the students more time to practice speaking English; 2) to teach them more on vocabulary, grammar, and pronunciation, for communicative purposes; 3) not to laugh at students' mistakes or let other students laugh at them; and 4) to consider about reducing the number of the students in English classes. Besides, further study was recommended in order to do wider researches that involve more than one campus or school.